A comparative study of the early Minangkabau and Bawean settlers in Gombak traditional villages: A case study of Kampung Simpang Tiga and Kampung Sg Chinchin - Mansor Majdin, Mohamad Firdaus; Mohd, Siti Hadija; Sulkafle, Mohamad Hazizie (ASIAN SCHOLARS NETWORK, 2025)
This paper comparatively examines key features of the early migrations of the Minangkabau (particularly the Minang community) and Bawean settlers to the state of Selangor, using Kampung Simpang Tiga and Kampung Sungai Chinchin as case studies. Preliminary research in these two traditional villages reveals a noteworthy presence of Minangkabau and Bawean communities, which interestingly reflect patterns of Sumatran migration into Malaya in the 19th and 20th centuries. This study explores, through historical analysis and fieldwork, the communities’ trajectories of migration, social integration, and economic contribution to their localities. There is yet an adequate comparative study that has been made to analyse these two dominant Indonesian settlers who were living relatively near to each other, albeit in separate settlements. By analysing their respective patterns of settlement, adaptation, and identity-making using socio-cultural and historical approaches, the paper highlights how both communities had lasting social and economic impacts in the areas they inhabited.